Engineering neuroimmune regulation: biomaterial and nanotechnology platforms for neuropathology diagnosis and targeted immunomodulation - Jackson, Mikayla S.; Porter, Lauren G.; Oakes, Robert S. (Frontiers in Immunology, 2026)
The immune system is a potent and interwoven regulator of neuropathology in the central nervous system (CNS). For example, gliomas, neurodegenerative diseases, and autoimmune neuroinflammation all have diverse etiology and pathogenesis. Yet, there are numerous similarities in immunological dysfunction between these neuropathological conditions. Synthesizing this knowledge could inform advanced diagnostics and therapeutic platforms. For instance, detection and precision management of neuroinflammation or blood-brain barrier integrity would be broadly applicable. Understanding the targetable or controllable immune pathways of these disorders and engineering local and systemic interventions are essential for improving disease prognosis. This review integrates and contrasts the biology, detection, and treatment of the aforementioned neuropathologies. First, immunological underpinnings and recent discoveries on the role of innate and adaptive immune cells are discussed. Second, diagnostics that span molecular and nanotechnology-based platforms are detailed for enhanced imaging and screening of neuroinflammation. Last, immunomodulatory therapeutics and the precision of biomaterial platforms for neuroimmune regulation are examined. Within this section on therapeutics, both clinical and experimental approaches are stratified by CNS-localized or systemic mechanism-of-action. Overall, the integration of immunotherapies, biomaterials, advanced drug delivery platforms, and precision medicine will be critical in overcoming current treatment limitations for neuropathology that have few or no therapeutic options.